The Semantics of Plurals, Focus, Degrees, and Times Essays in Honor of Roger Schwarzschild - Altshuler, Daniel; Rett, Jessica (Springer International Publishing : Imprint: Springer, 2019)
This volume is a tribute to Roger Schwarzschild's immense contributions in the formal semantics of nouns, focus, degrees and space, and tense and aspect. Collectively, the papers in the volume reveal parallels across ontological domains, in particular in the context of elements with internal structure, like plural sets, alternative sets, degree intervals, temporal intervals, and vectors. This research suggests that the structure of an entity could inform the semantic behavior of that entity just as much (if not more) than its semantic type or lexical category. And because these structures dictate the formation of semantic alternatives, it can help inform focus semantics and scalar implicature as well. Old questions on plurals, focus and degree expressions get new answers in this collection of papers in honor of Roger Schwarzchild. Roger Schwarzschild is one of the leading scholars in semantics, and the editors have been highly successful in requesting contributions by his teachers, peers and former students. Some papers have circulated in draft form for many years, and find their final home in this edited volume, which well reflects the state of the art in the field. Prof. dr. Henriëtte de Swart, Utrecht University, The Netherlands.